Journaling - Bending, Jan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
I use journaling in classes where a component of student learning involves reflection on the ways in which personal views impact the understanding, tolerance, and openness to new information about a subject. I also use journaling when I ask students to engage in service learning to help them process the experiences they have and to interpret those experiences sociologically.